Monocyte-directed RNAi targeting CCR2 improves infarct healing in atherosclerosis-prone mice - Majmudar, Maulik D. (2013)
BACKGROUND: Exaggerated and prolonged inflammation after myocardial infarction (MI) accelerates left ventricular remodeling. Inflammatory pathways may present a therapeutic target to prevent post-MI heart failure. However, the appropriate magnitude and timing of interventions are largely unknown, in part because noninvasive monitoring tools are lacking. We here employed nanoparticle-facilitated silencing of CCR2, the chemokine receptor that governs inflammatory Ly-6C(high) monocyte subset traffic, to reduce infarct inflammation in apoE(−/−) mice after MI. We used dual target PET/MRI of transglutaminase factor XIII (FXIII) and myeloperoxidase (MPO) activity to monitor how monocyte subset-targeted RNAi altered infarct inflammation and healing. METHODS AND RESULTS: Flow cytometry, gene expression analysis and histology revealed reduced monocyte numbers and enhanced resolution of inflammation in infarcted hearts of apoE(−/−) mice that were treated with nanoparticle-encapsulated siRNA. To follow extracellular matrix crosslinking non-invasively, we developed a fluorine-18 labeled PET agent ((18)F-FXIII). Recruitment of MPO-rich inflammatory leukocytes was imaged using a molecular MRI sensor of MPO activity (MPO-Gd). PET/MRI detected anti-inflammatory effects of intravenous nanoparticle-facilitated siRNA therapy (75% decrease of MPO-Gd signal, p<0.05) while (18)F-FXIII PET reflected unimpeded matrix crosslinking in the infarct. Silencing of CCR2 during the first week after MI improved ejection fraction on day 21 after MI from 29 to 35% (p<0.05). CONCLUSION: CCR2 targeted RNAi reduced recruitment of Ly-6C(high) monocytes, attenuated infarct inflammation and curbed post-MI left ventricular remodeling.